Evolution, Monitoring and Predicting Models of Rockburst Precursor Information for Rock Failure - Wang, Chunlai (Springer Nature, 2018)
Load/unload response ratio predicting of rockburst; Three-dimensional reconstruction of fissured rock; Nonlinear dynamics evolution pattern of rock cracks; Bayesian model for predicting rockburst